Supporting sustainable transport appraisals using stakeholder involvement and MCDA - Barfod, Michael Bruhn (Transport, 2018)
Appraisal processes for transport initiatives are often characterised by their complexity involving a wide range of impacts that need to be addressed and many stakeholders that attempt to influence the decisions to be made. The increasing interest for the environment and sustainable development in general has stressed the need for taking a broad perspective into account when addressing transport initiatives. This means that economic, social and environmental dimensions need to be considered simultaneously in the appraisal process. The focus on incorporating such sustainability considerations has set new demands for the appraisal process and has revealed an increasing need for involving stakeholders in the decision support process to capture all aspects of the often complex decision problems. Conventional appraisals within the transport area are often only based on cost-benefit analysis, which captures the impacts that can be assigned with a monetary value. Thus there is a need for a decision support system that is able to assess the effect of other types of impacts as well and include this in the appraisal. This paper seeks to fill this gap in research by proposing a methodology making use of planning workshops and multi-criteria decision analysis in combination to improve the decision support. In order to serve the purpose of promoting a more sustainable transport planning approach a proposal is made for how the methodology can be integrated in the current practice for appraisal of infrastructure projects in Denmark (and countries with similar approaches). The paper concludes that the approach allowing for active stakeholder participation in the appraisal process can serve as a helpful and effective decision support system in the quest for more sustainable solutions to transport problems.